A Case of Fat Embolism Syndrome with Cerebral Involvement in Sickle Cell Anemia. (4th July 2021) - Melvin, Rochelle G.; Liederman, Zachary; Arya, Sumedha; Rotin, Lianne; Lee, Christie M.
Abstract: Fat embolism syndrome (FES) is a rare condition that can occur as a complication of sickle cell disease. We describe a case of a patient with sickle cell disease (homozygous Hb S or HBB : c.20A>T) presenting with initial signs and symptoms consistent with a vaso-occlusive crisis (VOC). Within 24 hours, the patient developed evidence of coagulopathy, multi organ failure and a reduced level of consciousness (LOC) prompting intubation. A diagnosis of FES was made on the basis of the patient's clinical presentation, in conjunction with magnetic resonance imaging (MRI) of the brain revealing innumerable tiny foci of restricted diffusion, intracytoplasmic microvesicular fat on Sudan Red staining of bronchoalveolar lavage samples and evidence of a pulmonary shunt on echocardiogram bubble study. Red blood cell (RBC) exchange transfusion was initiated 3 days following initial presentation and no further exchange transfusions were needed on the basis of subsequent Hb S ( HBB: c.20A>T) levels. The LOC gradually improved and the patient was extubated 12 days following presentation. Neurological improvement was slow, with mild cognitive impairment initially evident at 3 months and no cognitive or neurological deficits remaining within 6 months of admission. This case highlights the importance of understanding the pathophysiology and clinical presentation of FES, as early exchange transfusion may improve survival in patients with sickle cell disease and FES.